Correction: MiR-277/4989 regulate transcriptional landscape during juvenile to adult transition in the parasitic helminth Schistosoma mansoni. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2022)
[This corrects the article DOI: 10.1371/journal.pntd.0005559.].